Nokia- The surprising success of textbook wisdom - Pantzar, Mika (2016)
What is the secret behind Nokia’s phenomenal success in mobile phones? More generally, how to succeed in a turbulent high technology market? Historical and comparative studies bring understanding not only about past phenomena, but also insights about current and coming ones. In this paper we compare Ford and General Motors in the 1920s and 1930s with Motorola and Nokia in the 1980s and 1990s. The insight from this comparison is how reinvention of the product, category, relative to the market incumbent’s market conceptualization, is a recipe for success. Nokia’s success in the 1990s was based on following the guidelines pioneered by General Motors in the 1920s: market segmentation, embracing the latest technological advances, and brand management in the pursuit of consumer repurchases. The article tells how Nokia addresses both GM’s legacy and changes in the business environment. At the end of our paper, we disuss the generalizability of our findings.